Hypertrophic obstructive cardiomyopathy with recurrent ventricular tachycardias: from catheter ablation and stereotactic radiotherapy to heart transplant-a case report - Kautzner, Josef; Hašková, Jana; Cvek, Jakub; Adamíra, Marek; Peichl, Petr (European heart journal. Case reports, 2024)
BACKGROUND: Management of hypertrophic obstructive cardiomyopathy (HOCM) is often challenging, depending on clinical manifestation. This case report illustrates the complex treatment of HOCM with associated recurrent ventricular arrhythmias. CASE SUMMARY: A 54-year-old female with HOCM diagnosed in 2012 underwent a failed attempt for alcohol septal ablation, implantation of an implantable cardioverter-defibrillator, and repeated radiofrequency ablations (including ablation of the septal bulge to reduce LV obstruction). For ventricular tachycardia (VT) recurrences, she had stereotactic arrhythmia radioablation with subsequent epicardial cryoablation from mini-thoracotomy, and endocardial ablation with pulsed field energy. The situation was finally solved by mechanical support and heart transplantation. DISCUSSION: A few important lessons can be learned from the case. First, radiofrequency ablation was used successfully to decrease left outflow tract obstruction. Second, stereotactic radiotherapy has been used after four previous endo/epicardial catheter ablations to decrease the recurrences of VT. Third, mini-thoracotomy was used after previous epicardial ablation with subsequent adhesions to modify the epicardial substrate with cryoenergy. Fourth, pulsed field ablation of atrial fibrillation resulted in an excellent therapeutic effect. Fifth, pulsed field ablation was also used to modify the substrate for VT, and was complicated by transient AV block with haemodynamic deterioration requiring mechanical support. Finally, a heart transplant was the ultimate solution in the management of recurrent VT.
Keywords: Hypertrophic cardiomyopathy; Case report; Electroanatomical mapping; Ventricular tachycardia; Stereotactic arrhythmia radioablation; Catheter ablation